Determinants of Increasing Company Value in Accounting Perspective - Galuh Dwi Pramesti; Mahameru Rosy Rochmatullah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the determinants of firm value enhancement from an accounting perspective in the consumer goods manufacturing sector listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The research method used is a quantitative approach with an associative causal type. The sample was selected using purposive sampling with specific criteria such as the completeness of financial statements and consistency in dividend distribution. The data used is secondary data obtained from the official IDX website and related companies. The independent variables in this study include dividend policy, profitability, and firm size, while firm value serves as the dependent variable. The results show that dividend policy does not affect firm value, profitability has a positive effect on firm value, and firm size also affects firm value. However, this study is limited to manufacturing companies and a three-year period, with the variables used being limited. Therefore, it is recommended that future research expand the sample scope and add other variables.